a). At first, we solve the following differential equation:
"x^2y''+xy'-y=0"
We look for solution in the following form:
"y=x^{\\alpha}."
After substitution we receive:
"\\alpha(\\alpha-1)x^{\\alpha}+\\alpha x^{\\alpha}-x^{\\alpha}=0"
From this we receive:
"\\alpha^2-1=0."
Thus, we have the solution "y=c_1x+c_2\\frac{1}{x}" , "c_1,c_2\\in\\mathbb{C}" .
Now, we set "y=c_1(x)x+c_2(x)\\frac{1}{x}" and add additional restriction:
"c_1'x+c_2'\\frac1x=0". The latter implies "c_1''x+c_1'+c_2''\\frac1{x}-c_2'\\frac1{x^2}=0" . We substitute "y" into "x^2y''+xy'-y=x^2e^x"
and get:
"x^2(c_1''x+2c_1'+c_2''\\frac1x-2c_2'\\frac1{x^2}+2c_2\\frac1{x^3})+x(c_1'x+c_1+c_2'\\frac1{x}-c_2\\frac{1}{x^2})-(c_1x+c_2\\frac{1}{x})=x^2e^x"
"x^2(c_1'-c_2'\\frac1{x^2})=x^2e^x"
Thus, we receive a system of equations:
"x^2(c_1'-c_2'\\frac1{x^2})=x^2e^x"
"c_1'x+c_2'\\frac1x=0"
From the latter we obtain:
"2c_1'x=xe^x"
Thus, "c_1(x)=\\frac12e^x+k_1" , "c_2(x)=-\\frac12(2-2x+x^2)e^x+k_2" , "k_1,k_2\\in\\mathbb{C}"
The resulting solution is "y=(\\frac12e^x+k_1)x+(-\\frac12(2-2x+x^2)e^x+k_2)\\frac{1}{x}" .
b). At first, we solve the equation: "y''+a^2y=0" . The solution is "y=c_1e^{i a x}+c_2e^{-i a x}"
We suppose that "y=c_1(x)e^{i a x}+c_2(x)e^{-i a x}" and "c_1'e^{i a x}+c_2'e^{-i a x}=0" . From the latter we get: "c_1''e^{i a x}+iac_1'e^{iax}+c_2''e^{-i a x}-iac_2'e^{-iax}=0" We substitute "y" into "y''+a^2y=\\frac{1}{sin \\,ax}" and receive "c_1''e^{i a x}+2i\\,a\\,c_1'e^{i a x}-c_1a^2e^{i a x}+c_2''e^{-i a x}-2iac_2'e^{-i a x}-c_2a^2e^{-i a x}+a^2(c_1(x)e^{i a x}+c_2(x)e^{-i a x})=\\frac{1}{sin \\,ax}"
"i\\,a\\,c_1'e^{i a x}-iac_2'e^{-i a x}=\\frac{1}{sin \\,ax}"
"c_1'e^{i a x}+c_2'e^{-i a x}=0"
"2i\\,a\\,c_1'e^{i a x}=\\frac{1}{sin \\,ax}"
"c_1'=-i\\frac{e^{-i a x}}{2a\\,sin \\,ax}"
"c_1=-\\frac{i}{2a}(\\frac{1}{a}ln(sin\\,ax)-ix+c)"
"c_2=\\frac{i}{2a}(\\frac{1}{a}ln(sin\\,ax)+ix+c)"
"y=-\\frac{i}{2a}(\\frac{1}{a}ln(sin\\,ax)-ix+c)e^{i a x}+\\frac{i}{2a}(\\frac{1}{a}ln(sin\\,ax)+ix+c)e^{-i a x}"
Answer: a) "y=(\\frac12e^x+k_1)x+(-\\frac12(2-2x+x^2)e^x+k_2)\\frac{1}{x}"
b) "y=-\\frac{i}{2a}(\\frac{1}{a}ln(sin\\,ax)-ix+c)e^{i a x}+\\frac{i}{2a}(\\frac{1}{a}ln(sin\\,ax)+ix+c)e^{-i a x}"
Comments
Leave a comment